2000
DOI: 10.1002/(sici)1097-4628(20000620)76:12<1799::aid-app10>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Effective thermal conductivity of three-phase styrene butadiene composites

Abstract: Transient plane source technique was used for the simultaneous measurement of thermal conductivity and thermal diffisivity of three-phase styrene butadiene rubber composites. Two series of styrene butadiene rubber composites were studied, having natural rubber as a variable filler in both the composites along with 10 phr of silica and clay, respectively. The measurements were done at room temperature and normal pressure. The experimental results show that there is a small variation in the thermal conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 14 publications
4
13
4
Order By: Relevance
“…Thus, embedding nanosilica particles in polyimide matrix enhances the composites thermal conductivity and lowers its thermal resistance, which may be useful for thermal performance applications. Fitting the observed increase in the thermal conductivity of the nanocomposites with the filler volume fraction ( Figure 11) exhibits a linear dependence, which is in agreement with that reported by Agrawal et al [24] of their measurements on the thermal conductivity of styrene-butadiene composites.…”
Section: Thermal Conductivity Resultssupporting
confidence: 91%
“…Thus, embedding nanosilica particles in polyimide matrix enhances the composites thermal conductivity and lowers its thermal resistance, which may be useful for thermal performance applications. Fitting the observed increase in the thermal conductivity of the nanocomposites with the filler volume fraction ( Figure 11) exhibits a linear dependence, which is in agreement with that reported by Agrawal et al [24] of their measurements on the thermal conductivity of styrene-butadiene composites.…”
Section: Thermal Conductivity Resultssupporting
confidence: 91%
“…Thus, dispersion of NaI phase in PEO matrix enhances the electrolyte thermal conductivity and lowers its thermal resistance, which may be useful to thermal performance applications. Fitting the observed increase in the thermal conductivity of the composites with the filler volume fraction ( Figure 11) exhibits a linear dependence which is in agreement with the report by Agrawal et al 23 for their measurements on the thermal conductivity of styrene-butadiene composites. Table 4 shows a comparison between the electrical and thermal conduction behaviors of the prepared PEO/NaI thin films as a function of NaI content.…”
Section: Results and Discussion Electrical Conductivity Resultssupporting
confidence: 90%
“…One of the methods adopted in industry to reduce the solidification time is to enhance the thermal conductivity of mould material by reinforcement of high thermal conductive filler into flexible polymer. A significant amount of research work was found in the literature where particulate conductive fillers were incorporated into polymer to increase its effective thermal conductivity [1][2][3][4][5][6][7][8][9][10]. Through experimental study, it has been observed that the solidification time in soft tooling process is significantly reduced by reinforcement of conductive filler into flexible polymeric mould material [11,12].…”
Section: Introductionmentioning
confidence: 99%